2008
DOI: 10.1080/09585190802404247
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated vs. liberal market HRM: the impact of institutionalization on multinational firms

Abstract: The impact of institutionalized contexts on the HRM activities of multinational firms has become a focus of increasing attention in recent literature. However, theories of how different types of business systems or market economies may influence HRM, and the impact of context on multinational corporations (MNCs) operating under these different conditions are still not fully tested. In this paper the influence of the extent of institutional embeddedness of different national contexts (based on varieties of capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 54 publications
1
94
0
8
Order By: Relevance
“…The outcome represents a complex interaction of both host and home country institutions, diluting country of origin pressures through infusing local features Farndale, Brewster & Poutsma, 2008).…”
Section: Mncs and Comparative Capitalismsmentioning
confidence: 99%
“…The outcome represents a complex interaction of both host and home country institutions, diluting country of origin pressures through infusing local features Farndale, Brewster & Poutsma, 2008).…”
Section: Mncs and Comparative Capitalismsmentioning
confidence: 99%
“…Linked to this would be the benefit gained by incorporating domestic only firms into future research studies and looking at establishing the similarity or variation in HRM practices between them and domestic-owned MNEs. Farndale et al (2008) previously demonstrated variation in the HRM approaches of domestic only firms, domestic MNEs and foreign MNEs. More particularly, research that explores whether HRM becomes a more important consideration to domestic firms looking at pursuing international business expansion and whether there is an increased emphasis as a firm goes through different stages of international growth would be a welcome addition to knowledge.…”
Section: Discussion Conclusion and Future Research Avenuesmentioning
confidence: 99%
“…The literature focusing on country of origin effects varies on focus from those primarily interested in specific issues such as employee representation and consultation (e.g., Gunnigle et al 2005) or corporate control mechanisms (e.g., Harzing and Sorge 2003) to ones that have somewhat greater breadth in terms of HRM practices (Farndale et al 2008). Pudelko and Harzing (2007) draw conclusions about the move towards dominant (US) practices based on analysis of 12 subjective, micro-focused, bipolar scale measures, covering recruitment, training, promotion, communication and employee incentives.…”
Section: The Challenge Of Identifying Dominant/global Best Practicesmentioning
confidence: 99%
See 2 more Smart Citations